VILLAGE ROLE IN REDUCING STUNTING AS AN EFFORT TO ACHIEVE THE SDGS OF SUKODONO VILLAGE SIDOARJO DISTRICT - Tri Nur Azizah; Isna Fitria Agustina (DIA: Jurnal Administrasi Publik, 2023)
This research was conducted with the aim of finding out about the implementation of village government policies in reducing the prevalence of stunting in Sukodono Village. The phenomenon of stunting is a phenomenon that is currently occurring and is included in the sustainability development goal indicator. Data shows that the prevalence rate of stunting in Indonesia is still quite high at 24%. The central government to local governments are trying hard to overcome this phenomenon. This is necessary because stunting has such a big impact on the growth of early childhood in Indonesia. This research method uses descriptive qualitative method with data collection using interviews, observation and documentation. The selection of informants in this case uses a purposive sampling method by selecting informants who are considered to understand the topic of the problem being raised. The results showed that the role of the Sukodono Village government according to the yeti theory approach contained four indicators, namely the availability of facilities and infrastructure where the village government had attempted to provide posyandu tools. The second is the availability of a budget where the Sukodono Village government has budgeted 60,000,000 for the stunting program. The three partnerships where there are three parties that play a role, namely the Village Government, Health Officers and the Regional General Hospital. Lastly is community participation where the people of Sukodono Village fully support the reduction of stunting rates.